Polyimide film for graphite sheet, its manufacturing method and graphite sheet manufactured therefrom
Patent Information
- Application Number
- JP2023530697
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-30
- Filing Date
- 2021-11-26
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-11-26
Smart Images

Figure 0007634675000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyimide film for graphite sheets, a manufacturing method thereof, and a graphite sheet manufactured from the polyimide film. More specifically, the present invention relates to a polyimide film for graphite sheets that is excellent in surface quality and thermal conductivity and can ensure a high thickness, a manufacturing method thereof, and a graphite sheet manufactured from the polyimide film. [Background technology]
[0002] In recent years, electronic devices have become lighter, smaller, thinner, and more highly integrated, which causes a lot of heat to be generated in the electronic devices. Such heat can shorten the life of the product or cause breakdowns or malfunctions. Therefore, thermal management for electronic devices has become an important issue. Graphite sheets have a higher thermal conductivity than metal sheets such as copper and aluminum, and are attracting attention as heat dissipation materials for electronic devices. In particular, research on thick graphite sheets (e.g., graphite sheets having a thickness of about 100 μm or more), which are advantageous in terms of heat acceptance compared to thin graphite sheets (e.g., graphite sheets having a thickness of about 40 μm or less), is actively progressing. Graphite sheets can be produced by various methods, for example, by carbonizing and graphitizing a polymer film. In particular, polyimide films have been attracting attention as polymer films for producing graphite sheets due to their excellent mechanical and thermal dimensional stability, chemical stability, etc.
[0003] A thick graphite sheet can be produced by carbonizing and graphitizing a thick polyimide film (e.g., a polyimide film having a thickness of about 100 μm or more). However, it is difficult to obtain a good-quality graphite sheet with a smooth surface and an undamaged graphite structure in the heat treatment process, resulting in a low yield. This is presumably because, assuming that carbonization and graphitization proceed almost simultaneously in the surface layer and the inside of a polyimide film, in the case of a thick polyimide film, the amount of sublimation gas generated from the inside is large, so that the graphite structure formed or being formed in the surface layer is likely to be damaged. Another possible cause is that the pressure increases significantly not only in the surface but also in the center of the film and the inside adjacent to it due to a relatively large amount of sublimation gas, causing damage to the graphite structure formed or being formed. Therefore, there is a strong need for a technology capable of producing high quality graphite sheets having a large thickness and having a perfect surface quality and graphite structure. Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a polyimide film for a graphite sheet which has excellent surface quality and thermal conductivity and can ensure a large thickness. Another object of the present invention is to provide a method for producing the polyimide film. It is still another object of the present invention to provide a graphite sheet produced from the polyimide film. [Means for solving the problem]
[0005] 1. According to one embodiment, there is provided a polyimide film for a graphite sheet, the polyimide film may have a thickness of 100 μm or more and a 1% weight loss thermal decomposition temperature of 480° C. or less as measured by thermogravimetric analysis (TGA). 2. According to another embodiment, there is provided a polyimide film for a graphite sheet, the polyimide film may have a thickness of 100 μm or more and an L* value of 40 or more as measured by a color difference meter. 3. In the first or second embodiment, the polyimide film may contain a sublimable inorganic filler. 4. In the third embodiment, the average particle size (D 50 ) may be 1 μm to 10 μm, and the sublimable inorganic filler may be contained in an amount of 0.15 parts by weight to 0.25 parts by weight per 100 parts by weight of the polyimide film. 5. In the third or fourth embodiment, the sublimable inorganic filler may include dibasic calcium phosphate, barium sulfate, calcium carbonate, or a combination thereof. 6. According to yet another aspect, there is provided a method for producing a polyimide film for a graphite sheet, which may include the steps of reacting a diamine monomer and a dianhydride monomer in a solvent to produce a polyamic acid solution, adding an imidizing agent, a dehydrating agent, a sublimable inorganic filler or a combination thereof to the polyamic acid solution to produce a precursor composition for a polyimide film, coating the precursor composition on a support and drying it to produce a gel film, and heat-treating the gel film to produce a polyimide film according to any one of the first to fifth embodiments. 7. In the sixth embodiment, the diamine monomer may include 4,4'-oxydianiline, 3,4'-oxydianiline, p-phenylenediamine, m-phenylenediamine, 4,4'-methylenedianiline, 3,3'-methylenedianiline, or a combination thereof, and the dianhydride monomer may include pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, oxydiphthalic anhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, or a combination thereof. 8. In the sixth or seventh embodiment, the drying may be performed at 30° C. to 200° C. for 15 seconds to 30 minutes. 9. In any one of the sixth to eighth embodiments, the heat treatment may be performed at 250° C. to 450° C. for 30 seconds to 40 minutes. 10. According to yet another embodiment, there is provided a graphite sheet. The graphite sheet may be formed by carbonizing and graphitizing the polyimide film of any one of the first to fifth embodiments or the polyimide film manufactured by the manufacturing method of any one of the sixth to ninth embodiments, and may have a thickness of 100 μm or more. 11. In the tenth embodiment, the graphite sheet has a thermal diffusion coefficient of 640 mm 2 / s or more. 12. In the tenth or eleventh embodiment, the graphite sheet is a polyimide film having 5 or less bright spots each having a major axis of 0.05 mm or more per unit area of 50 mm x 50 mm. Effect of the Invention
[0006] The present invention has an effect of providing a polyimide film for a graphite sheet which is excellent in surface quality and thermal conductivity and can ensure a large thickness, a method for producing the same, and a graphite sheet produced from the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise. In this specification, the terms "comprise" or "have" mean the presence of the features or components described in the specification, but do not preclude the possibility that one or more other features or components may be added. In interpreting the elements, it is understood that the margin of error is included even if there is no separate explicit description. Explain. In the present specification, when a numerical range is expressed as "a to b," "to" is defined as ≧a and ≦b.
[0008] The inventors of the present invention have conducted intensive research into polyimide films for graphite sheets which have excellent surface quality, thermal conductivity and can ensure a large thickness. As a result, they have found that when a graphite sheet is formed from a polyimide film which has a thickness of 100 μm or more, a 1 wt % weight loss thermal decomposition temperature of 480° C. or less as measured by thermogravimetric analysis (TGA), and / or an L* value of 40 or more as measured by a color difference meter, the time required for carbonization and / or graphitization can be shortened, and as a result, a thick graphite sheet with excellent surface quality and thermal conductivity can be produced, thereby completing the present invention.
[0009] The present invention will now be described in more detail. Polyimide film for thick graphite sheets The polyimide film according to one embodiment of the present invention may have a thickness of 100 μm or more, and a 1% weight loss thermal decomposition temperature measured by thermogravimetric analysis (TGA) of 480° C. or less (for example, 300° C. to 480° C., as another example, 400° C. to 480° C.). Within the above range, a high-thickness graphite sheet having excellent surface quality and thermal conductivity can be produced. Here, the thermogravimetric analysis (TGA) may be measured using a thermogravimetric analyzer (TGA 5500, TA Co.) at a heating rate of 10° C. / min from room temperature (23° C.) to 1,100° C., but is not limited thereto. For example, the 1 wt % weight loss thermal decomposition temperature of the polyimide film measured by thermogravimetric analysis (TGA) may be 460° C. or less, as another example, 450° C. or less, as yet another example, 440° C. or less, and as yet another example, 430° C. or less, and within the above range, it is more advantageous to produce a high thickness graphite sheet having excellent surface quality and thermal conductivity, but is not limited thereto.
[0010] The polyimide film according to another embodiment of the present invention may have a thickness of 100 μm or more and an L* value measured by a color difference meter of 40 or more. Within this range, a thick graphite sheet having excellent surface quality and thermal conductivity can be produced. Here, the L* value can be measured using a color difference meter (Ultra scan pro, Hunter Lab). For example, the L* value of the polyimide film measured by the color difference meter may be 45 or more, as another example, 50 or more, and as yet another example, 53 or more, and within the above range, it is more advantageous to produce a thick graphite sheet having excellent surface quality and thermal conductivity, but is not limited thereto. According to one embodiment, the thickness of the polyimide film may be 100 μm to 200 μm (e.g., 100 μm to 170 μm, for another example, 100 μm to 170 μm, and for yet another example, 100 μm to 150 μm), which is more advantageous for producing a high-thickness graphite sheet having excellent surface quality and thermal conductivity within the above range, but is not limited thereto.
[0011] According to an embodiment, the polyimide film may include a sublimable inorganic filler. The term "sublimable inorganic filler" refers to an inorganic filler that is sublimated by heat during the carbonization and / or graphitization process in the manufacture of a graphite sheet. When the polyimide film includes a sublimable inorganic filler, voids may be formed in the graphite sheet due to gas generated through sublimation of the sublimable inorganic filler during the manufacture of the graphite sheet. As a result, not only can the sublimation gas generated during the manufacture of the graphite sheet be smoothly exhausted, and a good quality graphite sheet can be obtained, but also the flexibility of the graphite sheet can be improved, ultimately improving the handleability and moldability of the graphite sheet. Examples of the sublimable inorganic filler include, but are not limited to, dibasic calcium phosphate, barium sulfate, calcium carbonate, etc. The average particle size (D 50 ) is 1μm to 10 The thickness of the sublimable inorganic filler may be 0.15 to 0.25 parts by weight (e.g., 0.2 to 0.25 parts by weight) based on 100 parts by weight of the polyimide film, and a good quality graphite sheet can be obtained within the above range, but is not limited thereto.
[0012] The polyimide film can be produced without limitation by using a conventional method known in the field of polyimide films. For example, the polyimide film can be produced by reacting a diamine monomer and a dianhydride monomer in a solvent to produce a polyamic acid solution, adding an imidizing agent, a dehydrating agent, a sublimable inorganic filler or a combination thereof to the polyamic acid solution to produce a precursor composition for a polyimide film, coating the precursor composition on a support and drying it to produce a gel film, and heat-treating the gel film to produce a polyimide film. First, a diamine monomer and a dianhydride monomer can be reacted in a solvent to prepare a polyamic acid solution.
[0013] The solvent is not particularly limited as long as it can dissolve the polyamic acid. For example, the solvent may contain an aprotic polar solvent. Examples of aprotic polar solvents include amide solvents such as N,N'-dimethylformamide (DMF) and N,N'-dimethylacetamide (DMAc), phenol solvents such as p-chlorophenol and o-chlorophenol, N-methyl-pyrrolidone (NMP), gamma butyrolactone (GBL), and diglyme, which may be used alone or in combination of two or more. In some cases, the solubility of the polyamic acid can be adjusted using auxiliary solvents such as toluene, tetrahydrofuran (THF), acetone, methyl ethyl ketone (MEK), methanol, ethanol, and water.
[0014] As the diamine monomer, various diamine monomers known in the art may be used without limitation within the scope of the present invention. For example, the diamine monomer may include 4,4'-oxydianiline, 3,4'-oxydianiline, p-phenylenediamine, m-phenylenediamine, 4,4'-methylenedianiline, 3,3'-methylenedianiline, or a combination thereof. In this case, it is possible to form a polyimide film that is favorable for molecular orientation, and it is more favorable to form a graphite sheet that has excellent thermal conductivity when carbonized and graphitized.
[0015] As the dianhydride monomer, various dianhydride monomers known in the art may be used without limitation within the scope of the present invention. For example, the dianhydride monomer may include pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, oxydiphthalic anhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, or a combination thereof. In this case, it is possible to form a polyimide film that is favorable for molecular orientation, and it is more favorable to form a graphite sheet having excellent thermal conductivity during carbonization and graphitization.
[0016] The diamine monomer and the dianhydride monomer are contained in the solvent in a substantially equimolar amount, and here, "substantially equimolar" means that the dianhydride monomer is contained in an amount of 99.8 mol% to 100.2 mol% based on the total number of moles of the diamine monomer. Reacting the diamine monomer and the dianhydride monomer in a substantially equimolar amount can be carried out, for example, as follows: (a) A method of adding all of the diamine monomer (or dianhydride monomer) to a solvent and then adding a substantially equimolar amount of the dianhydride monomer (or diamine monomer) to react with the dianhydride monomer (or diamine monomer); (b) A method of adding a part of the diamine monomer (or the dianhydride monomer) to a solvent, adding the dianhydride monomer (or the diamine monomer) in a ratio of 95 mol % to 105 mol % relative to the diamine monomer (or the dianhydride monomer), and then adding and reacting the diamine monomer and / or the dianhydride monomer in substantially equimolar amounts; (c) A first composition is formed by adding a part of the diamine monomer (or dianhydride monomer) and a part of the dianhydride monomer (or diamine monomer) in an excess amount into a solvent, and a second composition is formed by adding a part of the diamine monomer (or dianhydride monomer) and a part of the dianhydride monomer (or diamine monomer) in an excess amount into a separate solvent, and the first composition and the second composition are mixed and reacted, and at this time, if the monomer (or dianhydride monomer) is in excess in the first composition, the dianhydride monomer (or diamine monomer) is in excess in the second composition. In the above (a) to (c), the diamine monomer and the dianhydride monomer mean one or more (for example, one or two) diamine monomers and dianhydride monomers.
[0017] According to an embodiment, the polyamic acid may be included in an amount of 5 to 35 parts by weight based on 100 parts by weight of the polyamic acid solution. In this range, the polyamic acid solution has a molecular weight and viscosity suitable for forming a film. For example, the polyamic acid may be included in an amount of 5 to 30 parts by weight, or another example, 10 to 25 parts by weight based on 100 parts by weight of the polyamic acid solution, but is not limited thereto. According to one embodiment, the polyamic acid solution is heated at 23° C. and a shear rate of 1 s- 1 The viscosity may be 100,000 cP to 500,000 cP. In the above range, the polyamic acid has a predetermined molecular weight and is excellent in processability when forming a polyimide film. Here, the "viscosity" can be measured using a HAAKE Mars Rheometer. For example, the viscosity of a polyamic acid solution is measured at 23°C and a shear rate of 1 s- 1For example, the viscosity may be 100,000 cP to 450,000 cP, another example may be 150,000 cP to 400,000 cP, and yet another example may be 150,000 cP to 350,000 cP, but is not limited to these. According to an embodiment, the polyamic acid may have a weight average molecular weight of 100,000 g / mol to 500,000 g / mol. This range is more advantageous for producing a graphite sheet having excellent thermal conductivity. Here, the "weight average molecular weight" can be measured using gel permeation chromatography (GPC) with polystyrene as a standard sample. For example, the weight average molecular weight of the polyamic acid may be 100,000 g / mol to 450,000 g / mol, or another example, 150,000 g / mol to 400,000 g / mol, but is not limited thereto. Then, an imidizing agent, a dehydrating agent, a sublimable inorganic filler, or a combination thereof may be added to the polyamic acid solution to prepare a polyimide film precursor composition. The sublimable inorganic filler has been described above, so a description thereof will be omitted.
[0018] The "imidizing agent" is an agent that promotes a ring-closing reaction of polyamic acid. Examples of the imidizing agent include aliphatic tertiary amines, aromatic tertiary amines, and heterocyclic tertiary amines. Among them, heterocyclic tertiary amines may be used from the viewpoint of reactivity as a catalyst. Examples of heterocyclic tertiary amines include quinoline, isoquinoline, β-picoline, and pyridine, which may be used alone or in combination of two or more. The imidizing agent may be added in an amount of 0.05 mol to 3 mol (for example, 0.2 mol to 2 mol) per mol of amic acid group in the polyamic acid, and within the above range, sufficient imidization is possible and it is more advantageous to produce the polyamic acid in a film form, but the amount is not limited thereto.
[0019] The "dehydrating agent" is an agent that promotes the ring-closing reaction through a dehydrating effect on the polyamic acid. Examples of the dehydrating agent include aliphatic acid anhydrides, aromatic acid anhydrides, N,N'-dialkylcarbodiimides, lower aliphatic halides, halogenated lower aliphatic acid anhydrides, arylphosphatides, etc. Examples of suitable dehydrating agents include aliphatic acid anhydrides, such as thionyl dihalides and thionyl halides, which may be used alone or in combination of two or more. Among these, from the viewpoints of availability and cost, aliphatic acid anhydrides such as acetic anhydride, propionic anhydride, and lactic anhydride may be used. The dehydrating agent may be added in an amount of 0.5 mol to 5 mol (for example, 1 mol to 4 mol) per mol of amic acid group in the polyamic acid, and within the above range, sufficient imidization is possible and it is more advantageous to produce the polyamic acid in a film form, but the amount is not limited thereto. The precursor composition can then be coated onto a substrate and dried to produce a gel film.
[0020] Examples of the support include, but are not limited to, a glass plate, an aluminum foil, an endless stainless steel belt, a stainless steel drum, and the like. The application method is not particularly limited, and may be, for example, a casting method. Drying may be performed, for example, at 30°C to 200°C for 15 seconds to 30 minutes, and is more advantageous for producing a desired polyimide film of the present invention within the above range, but is not limited thereto. According to one embodiment, drying may be performed at 50°C to 150°C for 5 minutes to 20 minutes. In some cases, the method may further include a step of stretching the gel film to adjust the thickness and size of the final polyimide film and improve the orientation, and the stretching may be performed in at least one of the machine direction (MD) and the transverse direction (TD). The gel film can then be heat treated to produce a polyimide film.
[0021] The heat treatment may be performed, for example, at 250°C to 450°C for 30 seconds to 40 minutes, and the above range is more advantageous for producing the desired polyimide film of the present invention, but is not limited thereto. The heat treatment may be performed, for example, at 250°C (or 300°C or 350°C) to 430°C, for example, 250°C to 420°C, for example, 250°C to 410°C, for example, 250°C to 400°C, for example, 250°C to 390°C, for example, 5 minutes to 30 minutes, for example, 10 minutes to 30 minutes, for example, 15 minutes to 25 minutes, and the above range is more advantageous for producing a high-thickness graphite sheet having excellent surface quality and thermal conductivity, but is not limited thereto. The polyimide film manufactured by the above-mentioned manufacturing method is advantageous for realizing a graphite sheet having excellent surface quality and thermal conductivity and a high thickness.
[0022] High-thickness graphite sheet According to yet another aspect of the present invention, there is provided a graphite sheet formed by carbonizing and graphitizing the aforementioned polyimide film for graphite sheet. In this case, the graphite sheet may have a thickness of 100 μm or more (e.g., 100 μm to 400 μm), and thus has excellent heat capacity and is more advantageous for use as a heat dissipation means applied to electronic devices.
[0023] "Carbonization" is a process of pyrolyzing the polymer chains of a polyimide film to form a preliminary graphite sheet containing an amorphous carbon body, a non-crystalline carbon body, and / or an amorphous carbon body. Carbonization may be performed, for example, by increasing the temperature of the polyimide film to a temperature range of 1,100°C to 1,300°C at a rate of 0.3°C / min to 10°C / min, and this range is more advantageous for producing a high-thickness graphite sheet with excellent surface quality and thermal conductivity, but is not limited thereto. Carbonization may be performed under reduced pressure or in an inert gas atmosphere, and selectively, pressure may be applied to the polyimide film during carbonization using a hot press or the like to achieve high carbon orientation. The pressure at this time may be, for example, 5 kg / cm. 2 Other examples include 15kg / cm 2 Further examples include 25kg / cm 2 That's all. may be used, but is not limited to this.
[0024] "Graphitization" refers to a step of forming a graphite sheet by rearranging carbon in an amorphous carbon body, a non-crystalline carbon body, and / or an amorphous carbon body. Graphitization may be performed, for example, by raising the temperature of a preliminary graphite sheet to a temperature in the range of 2,500°C to 3,000°C at a rate of 0.3°C / min to 20°C / min, and this range is more advantageous for producing a high-thickness graphite sheet with excellent surface quality and thermal conductivity, but is not limited thereto. Graphitization may be performed under reduced pressure or in an inert gas atmosphere, and in some cases, pressure may be applied to the preliminary graphite sheet during graphitization using a hot press or the like to achieve high carbon orientation. The pressure at this time may be, for example, 100 kg / cm 2 Other examples include 200kg / cm 2 Further examples include 300kg / cm 2 It may be more than this, but is not limited to this.
[0025] According to one embodiment, the graphite sheet may have a thickness of 100 μm to 300 μm. According to another embodiment, the graphite sheet may have a thickness of 200 μm to 300 μm. The above range provides excellent handleability, but is not limited thereto. According to one embodiment, the graphite sheet has a thermal diffusion coefficient of 640 mm 2 / sec or more. In the above range, it is more advantageous to use it as a heat dissipation means applied to electronic devices. For example, the thermal diffusion coefficient of a graphite sheet is 650 mm 2 / s or more, for example, 670mm 2 / s or more, and as another example, 700 mm 2 / s or more, but is not limited to this. According to one embodiment, the graphite sheet may have 5 or less protrusions (bright spots) with major diameters of 0.05 mm or more per unit area of 50 mm x 50 mm. This range is more advantageous for use as a heat dissipation means applied to electronic devices. For example, the graphite sheet may have 3 or less bright spots, another example, 2 or less, another example, 1 or less, or yet another example, no bright spots per unit area of 50 mm x 50 mm, but is not limited thereto. The present invention will be described in more detail below with reference to examples. However, these are presented as preferred examples of the present invention and should not be construed as limiting the present invention in any way. EXAMPLES
[0026] Example 1 100 g of pyromellitic dianhydride as a dianhydride monomer, 196 g of 4,4'-oxydianiline as a diamine monomer, and 760 g of dimethylformamide as a solvent were mixed and reacted to prepare a polyamic acid solution having a viscosity of 200,000 cP. The polyamic acid solution was added with calcium phosphate dibasic (average particle size (D 50A precursor composition was prepared by adding 14 g of acetic anhydride as a dehydrating agent, 2 g of β-picoline as an imidizing agent, and 10 g of dimethylformamide as a solvent. The content of the sublimable inorganic filler used was 2,500 ppm based on the weight of the polyimide film. The precursor composition was cast onto a SUS plate (100SA, Sandvik) using a doctor blade and dried at 130° C. for 8 minutes to produce a gel film. The gel film was separated from the SUS plate and then heat-treated at 380° C. for 20 minutes to produce a polyimide film.
[0027] Example 2 A polyimide film was prepared in the same manner as in Example 1, except that the heat treatment temperature was changed from 380° C. to 400° C.
[0028] Example 3 A polyimide film was prepared in the same manner as in Example 1, except that the heat treatment temperature was changed from 380° C. to 420° C.
[0029] Comparative Example 1 A polyimide film was prepared in the same manner as in Example 1, except that the heat treatment temperature was changed from 380° C. to 460° C.
[0030] Evaluation example (1) 1% weight loss thermal decomposition temperature (T d 1%) (unit: °C): The polyimide films prepared in the examples and comparative examples were subjected to thermogravimetric analysis at a heating rate of 10°C / min from room temperature (23°C) to 1100°C using a thermogravimetric analyzer (TGA 5500, TA Corporation). (2) Color L*: The L* value was measured at room temperature using a color difference meter (Ultra scan pro, Hunter Labs). (3) Thermal diffusion coefficient (unit: mm 2 / s): The polyimide films produced in the Examples and Comparative Examples were carbonized from room temperature to 1200°C at a heating rate of 1°C / min, and then graphitized at a heating rate of 1.5°C / min from 1200°C to 2200°C, at a heating rate of 0.4°C / min from 2200°C to 2500°C, and at a heating rate of 8.5°C / min from 2500°C to 2800°C to produce graphite sheets. The graphite sheet thus produced was cut into a circular shape having a diameter of 25.4 mm to produce a sample, and the thermal diffusion coefficient of the sample was measured by a laser flash method using a thermal diffusivity measuring device (LFA 467, Netsch). (4) Bright spots (unit: number): The number of protrusions having a major axis of 0.05 mm or more per unit area of 50 mm x 50 mm was measured. [Table 1]
[0031] From Table 1, it can be seen that the thick graphite sheets prepared from the polyimide films of Examples 1 to 3, whose 1 wt % weight loss pyrolysis temperatures or L* values are within the range of the present invention, have higher thermal diffusion coefficients and less bright spots, and thus are superior in thermal conductivity and surface quality, compared to the thick graphite sheet prepared from the polyimide film of Comparative Example 1, whose 1 wt % weight loss pyrolysis temperatures or L* values are within the range of the present invention. Thus far, the present invention has been described with reference to the embodiments. Those skilled in the art will understand that the present invention can be embodied in modified forms without departing from the essential characteristics of the present invention. Therefore, the disclosed embodiments should be considered from an illustrative rather than a restrictive perspective. The scope of the present invention is defined by the claims, not the above description, and all differences within the scope of the equivalents thereof should be considered as included in the present invention. [Industrial Applicability]
[0032] The present invention has an effect of providing a polyimide film for a graphite sheet which is excellent in surface quality and thermal conductivity and can ensure a large thickness, a method for producing the same, and a graphite sheet produced from the same.
Claims
1. The thickness is 100 μm or more, A polyimide film for a graphite sheet, which has a 1 wt % weight loss thermal decomposition temperature of 480° C. or less as measured by thermogravimetric analysis (TGA), The polyimide film is produced by heat treating a gel film, the gel film is formed by drying a precursor composition comprising a polyamic acid; the polyamic acid is composed of a dianhydride monomer and a diamine monomer as polymerization units, the heat treatment temperature is 250° C. to 450° C., the dianhydride monomer comprises pyromellitic dianhydride, The polyimide film for graphite sheet, wherein the diamine monomer comprises 4,4'-oxydianiline.
2. The thickness is 100 μm or more, A polyimide film for graphite sheet, having an L* value of 40 or more as measured by a color difference meter, The polyimide film is produced by heat-treating a gel film, the gel film is formed by drying a precursor composition including a polyamic acid; the polyamic acid is composed of a dianhydride monomer and a diamine monomer as polymerization units, the heat treatment temperature is 250° C. to 450° C., the dianhydride monomer comprises pyromellitic dianhydride, The polyimide film for graphite sheet, wherein the diamine monomer comprises 4,4'-oxydianiline.
3. The polyimide film according to claim 1 or claim 2 contains a sublimable inorganic filler. Item 3. The polyimide film for a graphite sheet according to item 2.
4. The average particle size (D 50 ) is 1 μm to 10 μm, 4. The polyimide film for graphite sheet according to claim 3, wherein the sublimable inorganic filler is contained in an amount of 0.15 to 0.25 parts by weight per 100 parts by weight of the polyimide film.
5. 4. The polyimide film for graphite sheet according to claim 3, wherein the sublimable inorganic filler comprises dibasic calcium phosphate, barium sulfate, calcium carbonate, or a combination thereof.
6. A diamine monomer and a dianhydride monomer are reacted in a solvent to produce a polyamic acid solution; adding an imidizing agent, a dehydrating agent, a sublimable inorganic filler, or a combination thereof to the polyamic acid solution to prepare a precursor composition for a polyimide film; The precursor composition is coated on a support and dried to produce a gel film; 3. The method for producing a polyimide film for a graphite sheet according to claim 1 or 2, further comprising the step of heat-treating the gel film to produce a polyimide film, The temperature of the heat treatment is 250° C. to 450° C. the dianhydride monomer comprises pyromellitic dianhydride, The method for producing a polyimide film for a graphite sheet, wherein the diamine monomer comprises 4,4'-oxydianiline.
7. The diamine monomer further comprises 3,4'-oxydianiline, p-phenylenediamine, m-phenylenediamine, 4,4'-methylenedianiline, 3,3'-methylenedianiline, or a combination thereof; 7. The method for producing a polyimide film according to claim 6, wherein the dianhydride monomer further comprises 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, oxydiphthalic anhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, or a combination thereof.
8. The method for producing a polyimide film according to claim 6, wherein the drying is carried out at 30° C. to 200° C. for 15 seconds to 30 minutes.
9. The method for producing a polyimide film according to claim 6, wherein the heat treatment is carried out for 30 seconds to 40 minutes.
10. The method includes a step of carbonizing the polyimide film for graphite sheet according to claim 1 or 2 and a step of graphitizing the polyimide film for graphite sheet, The graphite sheet has a thickness of 100 μm or more, The thermal diffusivity of the graphite sheet is 640 mm 2 / s or more; The graphite sheet has 5 or less bright spots each having a major axis of 0.05 mm or more per unit area of 50 mm x 50 mm.
Citation Information
Patent Citations
High modulus graphite radiating fin
CN104310379A
Graphite film with insulating material
JP2004017504A
Heat conductive sheet
JP2006306068A
Graphite sheet polyimide film and production method thereof
JP2016017169A
Polyimide film and method for producing the same
JP2017043668A